1999
DOI: 10.1038/sj.jea.7500032
|View full text |Cite
|
Sign up to set email alerts
|

Reference range concentrations of N-acetyl-S-(2-hydroxyethyl)-L -cysteine, a common metabolite of several volatile organic compounds, in the urine of adults in the United States

Abstract: N-acetyl-S-(2-hydroxyethyl)-L-cysteine (2-hydroxyethyl mercapturic acid, HEMA) is a urinary metabolite of several hazardous chemicals, including vinyl chloride (VC), ethylene oxide (EO), and ethylene dibromide (EDB). Information about the levels of HEMA in the general population is useful for assessing human exposures to HEMA parent compounds, including VC, EO, and EDB. To establish reference range concentrations for HEMA, we analyzed urine samples from 412 adult participants in the Third National Health and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
3
14
1
Order By: Relevance
“…This agrees well with the median concentrations of 1.1 and 2.9 Ag/g creatinine, respectively, found by Calafat et al (19) in the frame of the National Health and Nutrition Examination Survey by isotope dilution high-performance liquid chromatography-atmospheric pressure chemical ionization-tandem mass spectrometry.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This agrees well with the median concentrations of 1.1 and 2.9 Ag/g creatinine, respectively, found by Calafat et al (19) in the frame of the National Health and Nutrition Examination Survey by isotope dilution high-performance liquid chromatography-atmospheric pressure chemical ionization-tandem mass spectrometry.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, HEMA in frozen urine samples seems to be stable, as suggested by Barr and Ashley (28). Finally, the median concentrations found in this study were very comparable with those reported by Calafat et al (19), which does not suggest that conservation over a 2-year period could have been a source of bias.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The potential interest of such biomarkers remains to be assessed, as for 1,3-butadiene, allyl chloride and 1,3-dichloropropene, in field or controlled studies to propose biological exposure indices. This is the case for the metabolite of ethylene oxide, 2-hydroxyethylmercapturic acid (HEMA), which is also a metabolite of vinyl chloride and ethylene dibromide (Calafat et al 1999;Popp et al 1994). As for acrylamide exposure, two different MAs have been measured in human urine and should be further investigated; AA-MA which results from the direct conjugation of GSH on acrylamide and GA-MA, the MA of glycidamide which is formed by epoxidation of acrylamide (Boettcher et al 2005).…”
Section: Analytical Approachesmentioning
confidence: 97%
“…As an illustration, a rapid LC-MS/MS method has been developed for the determination of MHBMA and DHBMA (metabolites of 1,3-butadiene) with LOD of 0.9 and 23 lg/l, respectively, in order to assess the smoking-related exposure to 1,3-butadiene (Urban et al 2003). A similar approach has been taken to determine the reference range of and the effect of smoking habits on HEMA (ethylene oxide metabolite) concentration in the urine of adults in the United States, using a LC-MS/MS method with a LOD of 0.68 lg/l (Calafat et al 1999). Similarly, LC-MS/MS methods have been validated for the measurement of PMA (benzene metabolite) with LODs of 0.1 lg/l (Melikian et al 1999) or 0.35 lg/l (Liao et al 2002).…”
Section: Analytical Approachesmentioning
confidence: 99%